Two-dimensional carbon nitride nanosheet layer as well as preparation method and application thereof
Through polar solvent assisted instantaneous high temperature peeling strategies, efficiently destroy the interductive force of the two -dimensional accumulation materials of carbon nitride, solve the problem of energy consumption and additional reagents in existing technologies, and achieve energy saving, green, and efficient nitrogen nitrogen nitrogen nitrogen nitrogen nitrogen Preparation of carbon nano tablets.
Patent Information
- Application Number
- CN202411925434.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing carbon nitride peeling methods have problems with energy consumption and additional reagents, and it is difficult to efficiently destroy the interlayer force of two-dimensional materials.
A polar solvent-assisted instantaneous high-temperature broad-spectrum two-dimensional material exfoliation strategy is used. NH4Cl solution is used in conjunction with a short-term high-temperature treatment process to peel off the carbon nitride two-dimensional layer stacked material, destroy the interlayer force, and obtain two-dimensional nitrogen. carbon nanosheets.
It achieves energy-saving, green and efficient destruction of the interlayer forces of carbon nitride two-dimensional layer stacking materials, and obtains two-dimensional carbon nitride nanosheets with excellent photocatalytic properties.
Smart Images

Figure CN119349517A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material preparation, and in particular relates to a two-dimensional carbon nitride nanosheet layer, a preparation method and application thereof. Background Art
[0002] In recent years, photocatalytic technology, which uses semiconductor materials with light response capabilities to drive solar energy, a green renewable energy source, to convert light energy into chemical energy, has received extensive attention in various fields of energy shortage and environmental governance. The characteristics of semiconductor materials such as light response and absorption capacity, specific surface area, charge transfer ability, conduction band and valence band position, and active sites directly determine the photocatalytic performance of semiconductor materials.
[0003] Carbon nitride was first reported by Professor Wang Xinchen in 2009. It has a two-dimensional planar structure similar to graphene, visible light response ability, and suitable energy band structure, and exhibits excellent photocatalytic hydrogen production performance. However, since carbon nitride is synthesized by high-temperature calcination of nitrogen-containing precursors, that is, the traditional solid-phase method, it has strong interaction forces between its layers. Therefore, carbon nitride synthesized by the solid-phase method exhibits an extremely small specific surface area. This is not conducive to the catalyst's response and absorption ability to light, nor is it conducive to the transfer of charge on the catalyst surface. In addition, in the field of photocatalytic synthesis, conversion, and degradation, a smaller specific surface area will reduce the contact area between the catalyst and the reactant, which is not conducive to the photocatalytic reaction.
[0004] In recent years, various methods of exfoliation of bulk carbon nitride have been developed. By destroying the interlayer forces of bulk carbon nitride and weakening the interlayer stacking phenomenon of carbon nitride synthesized by solid phase method, two-dimensional carbon nitride nanosheets are finally obtained, which has attracted extensive attention and research in the field of photocatalysis. The exfoliation methods of this idea mainly include: reheating process, acid treatment process, alkali treatment process, solvent thermal process, ultrasound or ultrasound-assisted organic solvent exfoliation process, etc. Li et al. synthesized carbon nitride aerogel with -CN through molten salt and self-assembly strategy, and achieved high CO2 reduction efficiency (Adv. Funct. Mater. 2024, 34: 2312634). Ding et al. successfully prepared modified carbon nitride with controllable carbon vacancies through simple acid treatment, and the corresponding Pd / CN-X catalyst showed excellent performance in the selective hydrogenation of phenol (ACS Catal. 2024,14: 3308-3319). In addition to its excellent photocatalytic performance, carbon nitride nanosheets can also be used as catalyst carriers to synthesize more functional photocatalysts. It can be seen that by using external force or acid, alkali, or organic solvent intercalation to destroy the interlayer effect, the layer stacking phenomenon of carbon nitride can be improved to obtain carbon nitride materials with nanosheets, and on this basis, high-efficiency catalysts can be further synthesized. Summary of the invention
[0005] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to overcome the energy consumption and additional reagent problems of the existing carbon nitride exfoliation methods, and to propose a two-dimensional carbon nitride nanosheet layer with energy-saving and green characteristics, which can efficiently destroy the interlayer forces of two-dimensional materials, and its preparation method and application.
[0006] In order to solve the technical problem, the technical solution adopted by the present invention is: On the one hand, the present invention provides a method for preparing a two-dimensional carbon nitride nanosheet layer, comprising: soaking a carbon nitride two-dimensional layer stacking material in a polar solvent, performing solid-liquid separation after continuous stirring, and quickly placing the soaked carbon nitride two-dimensional layer stacking material in a high-temperature furnace at a temperature of 400-800°C for insulation to obtain a two-dimensional carbon nitride nanosheet layer.
[0007] Preferably, the polar solvent is selected from any one of polar solvents such as NH4Cl solution, acetic acid solution, ethanol solution or isopropanol solution; the concentration of the NH4Cl solution is selected from any value in the range of 1-10 mg / L.
[0008] Preferably, the method specifically includes: soaking the carbon nitride two-dimensional layer stacking material in a polar solvent, stirring continuously for 0.5-5 hours and then performing solid-liquid separation, and quickly placing the soaked carbon nitride two-dimensional layer stacking material in a high-temperature furnace at a temperature of 400-800°C and keeping it warm for 1-30 minutes to obtain a two-dimensional carbon nitride nanosheet layer.
[0009] Preferably, the carbon nitride two-dimensional layer stacking material is prepared by solid phase calcination of a nitrogen-rich precursor, and the nitrogen-rich precursor is selected from at least one of urea, cyanamide, dicyandiamide, melamine, thiourea, and dimethylformamide.
[0010] Preferably, when preparing the carbon nitride two-dimensional layer stacking material by solid-phase calcining a nitrogen-rich precursor, the atmosphere used is nitrogen, and the nitrogen gas flow rate is 20-100 mL / min; the calcination temperature is 400-800°C; the calcination procedure includes heating to the target temperature in one step or heating to the target temperature in steps; the heating rate from room temperature to the target temperature is 0.1-10°C / min; and the calcination time is 1-6 h.
[0011] Preferably, the method further comprises dispersing the carbon nitride two-dimensional layer stacking material by means of sufficient grinding, ultrasound in water or ultrasound in an organic solvent, etc. before immersing the carbon nitride two-dimensional layer stacking material in a polar solvent.
[0012] Preferably, after the immersed carbon nitride two-dimensional layer stacking material is quickly placed in a high-temperature furnace at a temperature of 400-800°C for heat preservation, the method further comprises: cooling the sample by furnace cooling, slow cooling at room temperature, fast cooling with ice water or sudden cooling with liquid nitrogen.
[0013] Another aspect of the present invention provides a two-dimensional carbon nitride nanosheet layer prepared by the method for preparing a two-dimensional carbon nitride nanosheet layer described in any of the above technical solutions.
[0014] The present invention also provides a composite material, which uses the two-dimensional carbon nitride nanosheet layer described in the above technical solution as a component or carrier, including metal ion doping or nanoparticle loading, compounding with a large specific surface area carrier, compounding with a semiconductor as a co-catalyst, and constructing a micro heterojunction.
[0015] The present invention also provides the use of the two-dimensional carbon nitride nanosheet layer described in the above technical solution in photocatalytic degradation.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention provides a preparation method of a two-dimensional carbon nitride nanosheet layer, which adopts a polar solvent-assisted instantaneous high-temperature broad-spectrum two-dimensional material stripping strategy, utilizes a polar solvent NH4Cl solution, and cooperates with a high-temperature treatment process in a short time to strip the carbon nitride two-dimensional layer stacking material, and destroys the interlayer force of the carbon nitride two-dimensional layer stacking material in an energy-saving, green and efficient manner to obtain a sheet structure. During the operation of the stripping strategy, the carbon nitride two-dimensional layer stacking material is soaked in a polar solvent NH4Cl solution, and the polar molecule NH4Cl enters the interlayer of the carbon nitride two-dimensional layer stacking material. Subsequently, the soaked carbon nitride two-dimensional layer stacking material is quickly placed in a pre-heated high-temperature furnace to achieve instantaneous high-temperature heating of the soaked carbon nitride two-dimensional layer stacking material, and utilizes the instantaneous temperature difference change to make the NH4 + The rapidly vaporized and instantly overflowing NH3 will generate a supporting force, destroying the force between the stacked layers of the carbon nitride two-dimensional layer stacking material, and achieve the effect of peeling off the layers. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a scanning electron microscope image of the carbon nitride material prepared in Example 1 of the present invention; Figure 2 Another scanning electron microscope image of the carbon nitride material prepared in Example 1 of the present invention; Figure 3 This is a scanning electron microscope image of the carbon nitride material prepared in Example 2 of the present invention; Figure 4 This is a scanning electron microscope image of the carbon nitride material prepared in Example 3 of the present invention; Figure 5 This is a scanning electron microscope image of the carbon nitride material prepared in Comparative Example 1 of the present invention; Figure 6 This is a scanning electron microscope image of the carbon nitride material prepared in Comparative Example 2 of the present invention; Figure 7 An atomic force microscope (AFM) image of the carbon nitride material prepared in Example 1 of the present invention, wherein the upper image is an atomic force microscope (AFM) image, the lower image is a sample thickness curve corresponding to the position ae marked in the AFM image, curve a is a sample thickness curve corresponding to the position a marked in the AFM image, curve b is a sample thickness curve corresponding to the position b marked in the AFM image, curve c is a sample thickness curve corresponding to the position c marked in the AFM image, curve d is a sample thickness curve corresponding to the position d marked in the AFM image, and curve e is a sample thickness curve corresponding to the position e marked in the AFM image; Figure 8 This is an X-ray diffraction pattern of the carbon nitride material prepared in Example 1 of the present invention; Fig. 9 This is a comparison chart of the degradation performance of carbon nitride materials prepared in Example 1, Example 3, and Comparative Example 1 of the present invention; Fig.10 This is a cyclic stability performance diagram of Example 1 of the present invention. DETAILED DESCRIPTION
[0018] The technical scheme in the specific embodiment of the present invention is described in detail and completely below. Obviously, the described embodiment is only a part of the specific implementation of the overall technical scheme of the present invention, rather than all implementations. Based on the overall concept of the present invention, all other embodiments obtained by ordinary technicians in this field fall within the scope of protection of the present invention.
[0019] On one hand, the present invention provides a method for preparing a two-dimensional carbon nitride nanosheet layer, comprising: soaking a carbon nitride two-dimensional layer stacking material in a polar solvent, performing solid-liquid separation after continuous stirring, and quickly placing the soaked carbon nitride two-dimensional layer stacking material in a high-temperature furnace at a temperature of 400-800°C for heat preservation to obtain a two-dimensional carbon nitride nanosheet layer. Among them, the solid-liquid separation can be a process of centrifugation, centrifugation followed by air drying, centrifugation followed by vacuum drying, centrifugation followed by freeze drying, suction filtration, suction filtration followed by air drying, suction filtration followed by vacuum drying, suction filtration followed by freeze drying, evaporation to dryness, and rotary evaporation to dryness.
[0020] The above-mentioned preparation method adopts a polar solvent-assisted instantaneous high-temperature broad-spectrum two-dimensional material stripping strategy, and uses a polar solvent NH4Cl solution to cooperate with a high-temperature treatment process in a short period of time to strip the carbon nitride two-dimensional layer stacking material, thereby energy-saving, green, and efficiently destroying the interlayer force of the carbon nitride two-dimensional layer stacking material to obtain a layered structure. During the operation of the stripping strategy, the carbon nitride two-dimensional layer stacking material is soaked in a polar solvent NH4Cl solution, and the polar molecule NH4Cl enters the interlayer of the carbon nitride two-dimensional layer stacking material. Subsequently, the soaked carbon nitride two-dimensional layer stacking material is quickly placed in a pre-heated high-temperature furnace to achieve instantaneous high-temperature heating of the soaked carbon nitride two-dimensional layer stacking material, and the instantaneous temperature difference change is used to make the NH4 + The rapidly vaporized and instantly overflowing NH3 will generate a supporting force, destroying the force between the stacked layers of the carbon nitride two-dimensional layer stacking material, and achieve the effect of peeling off the layers.
[0021] It should be noted that the atmosphere that can be used in the high-temperature furnace for preheating includes inert gas (N2, Ar) or static air, and the gas flow rate of the inert gas is 20-100 mL / min. In addition, the operation process of the high-temperature furnace to provide an instantaneous temperature difference can also be a microwave radiation process, with a power of 50-100 W and a microwave time of 1-30 min.
[0022] In a preferred embodiment, the polar solvent is selected from any one of NH4Cl solution, acetic acid solution, ethanol solution or isopropanol solution; the concentration of the NH4Cl solution is selected from any value in the range of 1-10 mg / L. It is understood that the concentration of the NH4Cl solution can also be 2 mg / L, 3 mg / L, 4 mg / L, 5 mg / L, 6 mg / L, 7 mg / L, 8 mg / L, 9 mg / L and any point value in the range.
[0023] In a preferred embodiment, the process specifically includes: soaking the carbon nitride two-dimensional layer stacking material in a polar solvent, stirring continuously for 0.5-5 hours, and then performing solid-liquid separation, and quickly placing the soaked carbon nitride two-dimensional layer stacking material in a high-temperature furnace at a temperature of 400-800°C for 1-30 minutes to obtain a two-dimensional carbon nitride nanosheet layer. It is understood that the continuous stirring time can also be 1 hour, 2 hours, 3 hours, 4 hours, and any point value within the range; the temperature in the high-temperature furnace can also be 500°C, 600°C, 700°C, and any point value within the range; the insulation time can also be 5, 10, 15, 20, 25 minutes, and any point value within the range.
[0024] Furthermore, the following steps are included: (1) Weighing 0.5-20 g of melamine as a carbon nitride precursor, synthesizing an initial carbon nitride two-dimensional layer stacking material by a solid phase method through high temperature calcination, and fully grinding the material; (2) Weigh 0.05-10 g of the carbon nitride material synthesized in step (1), pour it into a 1-10 mg / L NH4Cl solution, and continue stirring for 0.5-5 h; (3) Raise the temperature of the high temperature furnace to the target high temperature of 400-800°C in advance; (4) performing solid-liquid separation on the two-dimensional material obtained in step (2) and soaked in a polar solvent; (5) Subsequently, the solid obtained in step (4) is quickly placed in the high-temperature furnace chamber heated in advance in step (3), and kept warm for 1-30 min; (6) The final exfoliation product is obtained by furnace cooling.
[0025] In a preferred embodiment, the carbon nitride two-dimensional layer stacking material is prepared by solid phase calcination of a nitrogen-rich precursor, and the nitrogen-rich precursor is selected from at least one of urea, cyanamide, dicyandiamide, melamine, thiourea, and dimethylformamide.
[0026] In a preferred embodiment, when preparing the carbon nitride two-dimensional layer stacking material by solid-phase calcination of a nitrogen-rich precursor, the atmosphere used includes an inert gas or static air, and the inert gas gas flow rate is 20-100 mL / min; the calcination temperature is 400-800°C; the calcination procedure includes heating to the target temperature in one step or heating to the target temperature in steps; the heating rate from room temperature to the target temperature is 0.1-10°C / min; the calcination time is 1-6 h. In the process of preparing the carbon nitride two-dimensional layer stacking material, the cooling process after high-temperature calcination by solid-phase method can be furnace cooling, slow cooling at room temperature, fast cooling with ice water, or rapid cooling with liquid nitrogen.
[0027] In a preferred embodiment, the carbon nitride two-dimensional layer stacking material is further dispersed by sufficient grinding, ultrasound in water or ultrasound in an organic solvent before immersing the carbon nitride two-dimensional layer stacking material in a polar solvent.
[0028] In a preferred embodiment, the immersed carbon nitride two-dimensional layer stacking material is quickly placed in a high-temperature furnace at a temperature of 400-800°C for insulation, and then the sample is cooled by furnace cooling, slow cooling at room temperature, fast cooling with ice water or sudden cooling with liquid nitrogen.
[0029] Another aspect of the present invention provides a two-dimensional carbon nitride nanosheet layer prepared by the method for preparing a two-dimensional carbon nitride nanosheet layer described in any of the above technical solutions.
[0030] The present invention also provides a composite material, which uses the two-dimensional carbon nitride nanosheet layer described in the above technical solution as a component or carrier, including metal ion doping or nanoparticle loading, compounding with a large specific surface area carrier, compounding with a semiconductor as a co-catalyst, and constructing a micro heterojunction. The synthesis method of the above composite material includes an impregnation method, a coprecipitation method, an in-situ calcination method, and an in-situ hydrothermal method.
[0031] The present invention also provides the use of the two-dimensional carbon nitride nanosheet layer described in the above technical solution in photocatalytic degradation.
[0032] In order to more clearly and in detail introduce the two-dimensional carbon nitride nanosheet layer, its preparation method and application provided by the embodiments of the present invention, a description will be given below in conjunction with specific embodiments.
[0033] Example 1 First, 10 g of urea was weighed as a carbon nitride precursor, and the temperature was raised to 550°C at a rate of 2.3°C / min under a nitrogen atmosphere (flow rate of 50 mL / min), and maintained for 4 h. The initial carbon nitride material was synthesized by high-temperature calcination by a solid-phase method. 0.5 g of ground carbon nitride was weighed and stirred in a 10 mg / L NH4Cl solution for 3 h, during which the muffle furnace was heated to 600°C. After stirring, the carbon nitride-NH4Cl suspension was separated from the solid by suction filtration, and the solid was quickly placed in a high-temperature furnace chamber that was heated in advance, and kept warm for 10 min. The exfoliated carbon nitride thin layer material was immediately taken out.
[0034] Example 2 First, 10 g of urea was weighed as a carbon nitride precursor, and the temperature was raised to 550°C at a rate of 2.3°C / min under a nitrogen atmosphere (flow rate of 50 mL / min), and maintained for 4 h, and the initial carbon nitride material was synthesized by high-temperature calcination by a solid phase method. 0.5 g of ground carbon nitride was weighed and stirred in a 10 mg / L NH4Cl solution for 3 h. After stirring, the carbon nitride-NH4Cl suspension was separated from the solid by suction filtration, and the solid was treated with microwaves for 10 min, and the carbon nitride material of Example 2 was immediately taken out.
[0035] Example 3 First, 10 g of melamine was weighed as a carbon nitride precursor, and the temperature was raised to 550°C at a rate of 2.3°C / min under a nitrogen atmosphere (flow rate of 50 mL / min), and maintained for 4 h, and the initial carbon nitride material was synthesized by high-temperature calcination by a solid-phase method. 0.5 g of ground carbon nitride was weighed and stirred in a 10 mg / L NH4Cl solution for 3 h, during which the muffle furnace was heated to 600°C. After stirring, the carbon nitride-NH4Cl suspension was separated from the solid by suction filtration, and the solid was quickly placed in a high-temperature furnace chamber that was heated in advance, and kept warm for 10 min, and immediately taken out to obtain the carbon nitride material of Example 3.
[0036] Comparative Example 1 First, 10 g of urea was weighed as a carbon nitride precursor, and the temperature was raised to 550°C at a rate of 2.3°C / min under a nitrogen atmosphere (flow rate of 50 mL / min), and maintained for 4 h, and the initial carbon nitride material was synthesized by high-temperature calcination by a solid phase method. 0.5 g of ground carbon nitride was weighed and quickly placed in a high-temperature furnace chamber heated to 600°C in advance, and kept warm for 10 min, and immediately taken out to obtain the carbon nitride material of Comparative Example 1.
[0037] Comparative Example 2 First, 10 g of urea was weighed as a carbon nitride precursor, and the temperature was raised to 550°C at a rate of 2.3°C / min under a nitrogen atmosphere (flow rate of 50 mL / min), and maintained for 4 h, and the initial carbon nitride material was synthesized by high-temperature calcination by a solid phase method. 0.5 g of ground carbon nitride was weighed and stirred in a 10 mg / L NH4Cl solution for 3 h. After stirring, the carbon nitride-NH4Cl suspension was separated from the solid and liquid by suction filtration, and the carbon nitride material of Comparative Example 2 was obtained after drying.
[0038] Performance Testing The carbon nitride catalysts of Example 1 and the comparative example were scanned by electron microscope. The results are as follows: Figures 1 to 6 As shown. Figures 1 to 6 It can be seen from the figure that the morphological characteristics of the carbon nitride nanosheet obtained by the preparation method described in the present invention. In addition, the importance of polar solvent combined with instantaneous high temperature process in the preparation of nano-thin layers, the polar solvent-carbon nitride sheet treated with microwaves did not unfold but was in a state of aggregation, and the carbon nitride materials prepared only by solvent immersion and only by instantaneous heating process all had nano-sheet structures. Figure 7 This is the atomic force microscope image AFM of Example 1. Five points with relatively scattered distribution were collected. The thickness of the obtained carbon nitride layer was about 10 nm, indicating that the carbon nitride prepared by this polar solvent-assisted high-temperature strategy was a nano-thin layer structure with a thickness of 10 nm. The X-ray diffraction pattern of the carbon nitride material prepared in Example 1 of the present invention is as follows: Figure 8 shown.
[0039] Conventional photocatalytic degradation experiment: The experiment was conducted at 25±2℃ with a xenon lamp simulating visible light irradiation (300 W Xe lamp, CEL-HXF 300, filter 420 nm). 100 mL of 20 mg / L methylene blue solution was placed in a photocatalytic reactor and 1 mol L -1 NaOH and HCl solutions were used to adjust the pH of the solution, and a specified amount of catalyst powder (0.25 g L -1 ). Stir continuously for 30 min in dark conditions to allow the system to reach adsorption-desorption equilibrium. Subsequently, add light source for irradiation to carry out photocatalytic degradation reaction. Samples are taken at a specific reaction time, centrifuged, and the supernatant is tested and the corresponding concentration is calculated to obtain the degradation efficiency.
[0040] Catalytic cycle test: The degradation rate of the catalyst detected by repeated experiments on organic pollutants is an important criterion for judging the stability of the catalyst. The catalyst dosage and other reaction conditions are kept consistent in repeated experiments. The catalyst collected through multiple degradation experiments can ensure that the catalyst dosage is sufficient after each cycle test. The specific experimental operation is as follows: After the catalytic test, solid-liquid separation is performed by centrifugation, and the catalyzed catalyst is washed multiple times with deionized water and alcohol, directly collected after vacuum drying, and then reused for degradation experiments. The specific catalytic experimental steps are the above-mentioned degradation experimental steps.
[0041] Example 1, the conventional photocatalytic degradation results of the comparative example are as follows Fig. 9 As shown in the figure, it can be seen that due to the nano-thin layer morphology of Example 1, Example 1 shows the best photocatalytic degradation effect compared with the comparative example. At the same time, the cycle performance test of Example 1 was carried out ( Fig.10 ), Example 1 showed excellent recycling ability, which fully demonstrated its practical application potential in the field of water pollution control.
Claims
1. A method for preparing a two-dimensional carbon nitride nanosheet layer, characterized in that: include: The carbon nitride two-dimensional layer stacking material is immersed in a polar solvent, and solid-liquid separation is performed after continuous stirring. The immersed carbon nitride two-dimensional layer stacking material is quickly placed in a high-temperature furnace at a temperature of 400-800°C for insulation to obtain a two-dimensional carbon nitride nanosheet layer.
2. The method for preparing a two-dimensional carbon nitride nanosheet layer according to claim 1, characterized in that: The polar solvent is selected from any one of NH4Cl solution, acetic acid solution, ethanol solution or isopropanol solution; the concentration of the NH4Cl solution is selected from any value between 1 and 10 mg / L.
3. The method for preparing a two-dimensional carbon nitride nanosheet layer according to claim 1, characterized in that: Specifically include: The carbon nitride two-dimensional layer stacking material is immersed in a polar solvent, and after continuous stirring for 0.5-5 hours, solid-liquid separation is performed. The immersed carbon nitride two-dimensional layer stacking material is quickly placed in a high-temperature furnace at a temperature of 400-800°C and kept warm for 1-30 minutes to obtain a two-dimensional carbon nitride nanosheet layer.
4. The method for preparing a two-dimensional carbon nitride nanosheet layer according to claim 1, characterized in that: The carbon nitride two-dimensional layer stacking material is prepared by calcining a nitrogen-rich precursor by a solid phase method, and the nitrogen-rich precursor is selected from at least one of urea, cyanamide, dicyandiamide, melamine, thiourea, and dimethylformamide.
5. The method for preparing a two-dimensional carbon nitride nanosheet layer according to claim 4, characterized in that: When the carbon nitride two-dimensional layer stacking material is prepared by solid-phase calcining a nitrogen-rich precursor, the atmosphere used is nitrogen, and the nitrogen gas flow rate is 20-100 mL / min; the calcination temperature is 400-800°C; the calcination procedure includes heating to the target temperature in one step or heating to the target temperature in steps; the heating rate from room temperature to the target temperature is 0.1-10°C / min; and the calcination time is 1-6h.
6. The method for preparing a two-dimensional carbon nitride nanosheet layer according to claim 1, characterized in that: The method further comprises dispersing the carbon nitride two-dimensional layer stacking material by sufficient grinding, ultrasonication in water or ultrasonication in an organic solvent before immersing the carbon nitride two-dimensional layer stacking material in a polar solvent.
7. The method for preparing a two-dimensional carbon nitride nanosheet layer according to claim 1, characterized in that: The soaked carbon nitride two-dimensional layer stacking material is quickly placed in a high-temperature furnace with a temperature of 400-800°C for heat preservation, and then the sample is cooled by furnace cooling, slow cooling at room temperature, fast cooling with ice water or sudden cooling with liquid nitrogen. 8 . The two-dimensional carbon nitride nanosheet layer prepared according to the method for preparing a two-dimensional carbon nitride nanosheet layer according to claim 1 .
9. A composite material, characterized in that: The two-dimensional carbon nitride nanosheet layer according to claim 8 is used as a component or carrier, including metal ion doping or nanoparticle loading, compounding with a large specific surface area carrier, compounding with a semiconductor as a co-catalyst, and constructing a micro heterojunction.
10. Use of the two-dimensional carbon nitride nanosheet layer according to claim 8 in photocatalytic degradation.
Citation Information
Patent Citations
Graphite-phase carbon nitride (g-C3N4) material and preparation method and application thereof
CN105126893A
Adsorption material as well as preparation method and application thereof
CN109107522A
SBR biofilm carrier recirculation SBR system by airlift pump
KR1020250015140A